ANALISIS PEMBIAYAAN MUDHARABAH, MUSYARAKAH DAN MURABAHAH UNTUK MENINGKATKAN PENDAPATAN PADA PT BANK SYARIAH MANDIRI CABANG MEDAN AKSARA - Edisahputra Nainggolan (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
The purpose of    this study was to determine and analyze the cause of a large Financing income  received  while  small,  and  to  investigate  the  causes  of  financing  products  for  the  results (profit sharing) channeled smallest of murabahah financing and Musyarakah. Research  approaches  used  descriptive  research  approaches,  data  collection  techniques used in this study interviews and documentation. Data analysis techniques used in this research is descriptive  analysis  technique  that  is  by  collecting  data  and  classifying  data  obtained  from  the company with the existing theory so as to provide a clear picture of the object being studied.Results showed Financing great while revenues received by little it is because of financing problems in the implementation of the payment of financing by the customer that  happens things like financing is not smooth, the financing of which the debtor does not meet the requirements that were promised, and these costs are not on schedule installments, troubled financing is one of the definite  risks  faced  by  each  bank  because  the  risk  is  often  also  called  credit  risk.  and  financing products for the results (Mudarabah) channeled smallest of Murabahah financing and Musyarakah and this is because of financing is financing with a high degree of risk and should be based on a strong element of trust. And the uncertainty of revenue to be earned as well as concerns about the loss or fraud is becoming the main cause.Keywords:  Mudarabah, Musyarakah and Murabahah, Mudarabah Income from Musharakah and Murabahah